Body Size Adaptation Alters Perception of Test Stimuli, Not Internal Body Image - Ambroziak, Klaudia B.; Azañón, Elena; Longo, Matthew R. (Frontiers in Psychology, 2019)
Recent studies have reported that adaptation to extreme body types produces aftereffects on judgments of body normality and attractiveness, and also judgments of the size and shape of the viewer’s own body. This latter effect suggests that adaptation could constitute an experimental model of media influences on body image. Alternatively, adaptation could affect perception of test stimuli, which should produce the same aftereffects for judgments about participant’s own body or someone else’s body. Here, we investigated whether adaptation similarly affects judgments about one’s body and other bodies. We were interested in participants’ own body image judgements, i.e. we wanted to measure the mental representations to which the test stimuli were compared to and not the perception of test stimuli per se. Participants were adapted to pictures of thin or fat bodies and then rated whether bodies were fatter or thinner than either: their own body, an average body (Experiment 1) or the body of another person (Experiments 2-3). By keeping the visual stimuli constant but changing the task/type of judgement, i.e. the internal criterion participants are asked to judge the bodies against, we investigated how adaptation affects different stored representations of bodies, specifically. own body image vs representations of others. After adaptation, a classic aftereffect was found, with judgments biased away from the adapting stimulus. Critically, aftereffects were nearly identical for judgments of one’s own body and for other people’s bodies. These results suggest that adaptation affects body representations in a generic way and may not be specific to the own body image.